A flexible architecture for client-side adaptation - Firmenich, Sergio (2012)
Currently the Web allows users to perform complex tasks which involve different Web applications. Anyway they still have to face these tasks in a handcrafted way. Although it is possible to build service-based software, such as mashups, to combine data and information from different providers, many times this approach has limitations. In this paper we present an approach for Client-Side Adaptation aimed to support complex concern-sensitive and task-based adaptations with user-collected data. Our approach improves user experience by supporting user tasks among several Web applications.